Secondary battery and electronic device
By adjusting the coating amount and proportion of the positive and negative electrode materials of lithium-ion batteries and optimizing the material layer structure, the problem of poor performance of lithium-ion batteries at high and low temperatures is solved, and the effects of high capacity recovery rate and low DC resistance are achieved.
Patent Information
- Application Number
- CN202310782338.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
Existing lithium-ion batteries have poor performance under high and low temperature conditions, and it is difficult to meet the high and low temperature performance requirements at the same time.
By controlling the coating amount and proportion of the positive electrode and negative electrode materials, the single-side coating amount of the positive electrode material layer is 45-120g/m2, and the single-side coating amount of the negative electrode material layer is 15-50g/m2, and the positive electrode and The proportion of the negative electrode material layer is (1.4-3): 1, and the thickness and active material content of the material layer are optimized, and combined with appropriate conductive agents and binders to form an efficient electrode structure.
It realizes high capacity recovery rate at high temperatures and low DC resistance at low temperatures, significantly improving the high and low temperature performance of secondary batteries.
Abstract
Description
Technical Field
[0001] The present invention relates to a secondary battery and an electronic device. Background Art
[0002] At present, compared with traditional lead-acid, nickel-cadmium, nickel-metal hydride and other secondary batteries, lithium-ion batteries have the advantages of high specific energy and low self-discharge, and have been widely used in electronic devices such as mobile phones, notebook computers, and cameras. With the continuous development of secondary batteries, in order to obtain secondary batteries with better electrical performance, the industry's requirements for secondary battery performance are constantly improving.
[0003] Lithium-ion batteries are composed of negative plates, positive plates, electrolytes, and separators between the positive and negative plates to prevent short circuits. For example, the negative plate is a carbonaceous material fixed on the current collector that absorbs / releases lithium ions; the positive plate is a composite oxide fixed on the current collector that absorbs / releases lithium ions; and the electrolyte is a solution containing a non-protonic organic solvents such as LiPF6.
[0004] The positive and negative plates are made into thin plates or foils, and then the electrode plates and the separators between them are stacked or spirally wound in sequence to form a battery core. This battery core is then placed in a stainless steel, nickel-plated iron, or lighter aluminum metal shell, or a laminated Al soft-package film battery container, and then injected with electrolyte and sealed to form a battery.
[0005] However, in the field of lithium-ion batteries, it is currently difficult to ensure that the secondary batteries have both good high-temperature performance and low-temperature performance. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a secondary battery and an electronic device in order to overcome the defects of the existing secondary battery in terms of poor high temperature performance and poor low temperature performance. The secondary battery of the present invention has excellent high temperature performance and low temperature performance, that is, it has a high capacity recovery rate at high temperature and a smaller direct current resistance (DCR) at low temperature.
[0007] In the art, thick coating and high compaction density are usually used for the positive and negative electrodes of secondary batteries to make the battery core have a large continuous and instantaneous discharge rate, but it cannot meet its high and low temperature performance; if the coating amount is simply reduced, the energy density of the secondary battery will be reduced, and the high and low temperature performance will not be met. Therefore, how to simultaneously meet the high and low temperature performance of the secondary battery has always been a difficult problem to be solved by those skilled in the art.
[0008] The inventors of the present application creatively obtained a secondary battery having both excellent high-temperature performance and low-temperature performance by controlling the coating amount and ratio of the positive and negative electrode materials.
[0009] The present invention mainly solves the above technical problems through the following technical solutions.
[0010] In a first aspect, the present invention provides a secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector;
[0011] The single-sided coating amount a1 of the positive electrode material layer is 45-120 g / m 2 ;
[0012] The single-sided coating amount a2 of the negative electrode material layer is 15-50 g / m 2 ;
[0013] The a1:a2 is (1.4-3):1.
[0014] In a second aspect, the present invention provides an electronic device comprising the secondary battery as described above.
[0015] The positive and progressive effects of the present invention are:
[0016] The secondary battery of the present invention has better high-temperature performance and low-temperature performance, that is, has a high capacity recovery rate at high temperature and has a smaller direct current resistance (DCR) at low temperature. DETAILED DESCRIPTION
[0017] Secondary battery
[0018] A first aspect of the present invention provides a secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector;
[0019] The single-sided coating amount a1 of the positive electrode material layer is 45-120 g / m 2 ;
[0020] The single-sided coating amount a2 of the negative electrode material layer is 15-50 g / m 2 ;
[0021] The a1:a2 is (1.4-3):1.
[0022] In the present invention, the coating amount is the mass of the positive electrode or negative electrode material layer per unit area.
[0023] In some embodiments, the single-sided coating amount a1 of the positive electrode material layer is 45-90 g / m 2, for example 45g / m 2 , 50g / m 2 , 70g / m 2 or 90g / m 2 .
[0024] In some embodiments, the single-sided coating amount a2 of the negative electrode material layer is 15-35 g / m 2 , for example 18g / m 2 , 20g / m 2 , 25g / m 2 , 26g / m 2 , 30g / m 2 or 34g / m 2 .
[0025] In some embodiments, a1:a2 is (2-3):1.
[0026] Those skilled in the art should know that the NP ratio is the ratio of the capacity of the negative electrode plate to the capacity of the positive electrode plate, and its calculation formula is: NP ratio = (negative electrode gram capacity × negative electrode coating amount × negative electrode active material content ratio) / (positive electrode gram capacity × positive electrode coating amount × positive electrode active material content ratio). Among them, the negative electrode active material content ratio refers to the mass ratio of the negative electrode active material to the negative electrode material layer; the positive electrode active material content ratio refers to the mass ratio of the positive electrode active material to the positive electrode material layer.
[0027] In some embodiments, the NP ratio is (1-2):1, where the NP ratio is the ratio of the capacity of the negative electrode plate to the capacity of the positive electrode plate.
[0028] In a specific embodiment, the NP ratio is (1-1.2):1, for example 1:1, 1.02:1, 1.08:1, 1.2:1.
[0029] In some embodiments, the thickness of the positive electrode material layer ranges from 42 to 76.5 μm, preferably from 46 to 76.5 μm; the thickness of the positive electrode material layer refers to the thickness of the coating layer containing the positive electrode active material on one side of the positive electrode current collector.
[0030] In some embodiments, the thickness of the negative electrode material layer ranges from 14 to 43.5 μm, preferably from 14 to 43.5 μm; the thickness of the negative electrode material layer refers to the thickness of the coating layer containing the negative electrode active material on one side of the negative electrode current collector.
[0031] In the present invention, the secondary battery may be a lithium-ion battery, which generally comprises: a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte.
[0032] In some embodiments, in the positive electrode material layer, the positive electrode active material includes a lithium-containing composite oxide, including but not limited to one or more of lithium iron phosphate materials, lithium iron manganese phosphate materials, nickel cobalt manganese ternary materials and lithium-rich manganese-based materials. Specific examples include LiMnO2, LiFeO2, LiMn2O4, Li2FeSiO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi5CO2Mn3O2, Li z Ni (1-x-y) Co x M y O2 (wherein 0.01≤x≤0.20, 0≤y≤0.20, 0.97≤z≤1.20, M represents at least one element selected from Mn, V, Mg, Mo, Nb and Al), LiFePO4 and Li z CO (1-x) M x O2 (wherein 0≤x≤0.1, 0.97≤z≤1.20, and M represents at least one element selected from the group consisting of Mn, Ni, V, Mg, Mo, Nb and Al).
[0033] Among them, NCM generally refers to nickel-cobalt-manganese ternary materials (LiNi x Co y Mn z O2, also written as LiNi 1-x-y Co x Mn y O2, where x, y and z are selected from different value ranges according to actual design, and x+y+z=1; where if doped with other elements, LiNi x Co y Mn z Me p O2, Me is selected from one or more combinations of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, Al); NCA generally represents Li x Ni 1-y-z Co y Al z O2; LFP stands for lithium iron phosphate (LiFePO4); LMFP / LFMP stands for lithium iron manganese phosphate (LiMn 1-x Fe x PO4 (x is selected from a suitable value range)).
[0034] Li 1+a [Ni x Co y M z ]O 2-b Ab , 0.7≤x<1, 0≤y<0.3, 0≤z<0.3, -0.2 <a<0.2,0≤b<0.2,
[0035] x+y+z=1; wherein the M element includes one or more of Mn, Al, Ti, Zr, Mg, Sr, W, Mo, B, V, Se, Nb, Ru, Rh, Pd, Sb, Te, Ce, Ca, Zn, Y and W, and the A element includes one or more of F, N, Cl, S and P.
[0036] In some embodiments, in the negative electrode material layer, the negative electrode active material includes a material that can embed and de-embed lithium. It includes but is not limited to carbon materials such as crystalline carbon (natural graphite and artificial graphite, etc.), amorphous carbon, carbon-coated graphite and resin-coated graphite, or oxide materials such as indium oxide, silicon oxide, tin oxide, lithium titanate, zinc oxide, lithium oxide, etc., and can also be lithium metal or a metal material that can form an alloy with lithium. Metal materials that can form alloys with lithium are, for example, Cu, Sn, Si, Co, Mn, Fe, Sb and Ag. Binary or ternary materials containing these metals and lithium can also be used as negative electrode active materials. These negative electrode active materials can be used alone or in combination of two or more. From the perspective of high energy density, carbon materials such as graphite can also be used in combination with Si, Si alloys, Si oxides and other Si-based materials.
[0037] In some embodiments, the positive electrode material layer and the negative electrode material layer contain primary particles and / or secondary particles; primary particles refer to a single fine grain or a single original grain; secondary particles refer to a plurality of small grains (original particles) formed by agglomeration. Dv50: median particle size, refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of a sample reaches 50%, and the unit of measurement is μm.
[0038] Binders, conductive agents and other substances are usually added to the positive electrode active materials and the negative electrode active materials. The added amount can be adjusted between 1% and 50% of the total amount of the positive electrode active materials according to different needs.
[0039] Conductive agents are reagents used to ensure that the electrode has good charge and discharge performance. Examples include graphite materials such as natural graphite and artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon black materials, conductive fibers such as carbon fibers and metal fibers, metal powders such as carbon fluoride powder, aluminum powder, nickel powder and other metal powders, conductive whiskers such as zinc oxide and potassium titanate, and conductive metal oxides such as titanium dioxide or polyphenylene derivatives. Super P: Super P-Li, a positive electrode powder conductive agent. CNT: Carbon Nano Tube, short for carbon nanotubes, negative electrode conductive agent.
[0040] The binder is a component that helps the active material to bind to the conductive agent and helps the active material to bind to the current collector. It can usually be selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber and various copolymers. PVDF: Polyvinylidene Fluoride, a binder used in positive electrode slurry. CMC: Carboxymethyl Cellulose, a binder used in negative electrode slurry. SBR: Polymerized Styrene Butadiene Rubber, a binder used in negative electrode slurry.
[0041] The active material, the conductive agent, the binder, etc. are mixed with a solvent to form a slurry. The solvent is preferably N-methylpyrrolidone (NMP).
[0042] The current collector is a substrate supporting the electrode active material, usually a metal foil with a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The current collector usually has a smooth surface, but fine lines can also be formed on its surface to increase the adhesion between the positive electrode active material and the current collector. In addition to the foil, the current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0043] The separator provided between the positive electrode and the negative electrode uses an insulating film with high ion permeability and high mechanical strength. The separator is typically 9-18 μm thick, 5-300 μm pore size, 180-380 s / 100 mL air permeability, and 30% to 50% porosity. As the separator, a sheet or non-woven fabric made of an olefin polymer such as polypropylene, glass fiber or polyethylene, which has chemical resistance and hydrophobicity, is used.
[0044] The electrolyte used in the lithium ion battery prepared as above generally includes a non-aqueous solvent, a lithium salt, and an additive.
[0045] As the lithium salt, at least one of LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), LiBF2(C2O4) (abbreviated as LiDFOB), LiN(SO2RF)2, and LiN(SO2F)(SO2RF) can be cited. Preferably, the content of the lithium salt in the electrolyte is 5% to 20%.
[0046] The non-aqueous solvent may be a conventional non-aqueous solvent in the art, preferably an ester solvent, more preferably a carbonate solvent. The carbonate solvent is preferably one or more of ethylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0047] The additive is preferably one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), dithiothreitol (DTD), vinylene sulfate, 1,3-propane sultone (PS), propene sultone and 1,4-butane sultone. The conventional amount of the additive in the electrolyte is 1%-4% of the electrolyte, for example, 2%.
[0048] The present invention is described by taking lithium-ion secondary batteries as an example. Lithium-ion secondary batteries can be roughly divided into soft-pack batteries, hard-shell batteries and cylindrical batteries according to the shell type. Although the three types of batteries have different external shell forms, the combination system of positive and negative electrodes and electrolyte materials assembled into the battery is common.
[0049] The specific embodiments below use small soft-pack batteries / large soft-pack batteries as examples to conduct electrochemical and other performance tests.
[0050] The preparation method of the secondary lithium battery (small cell) of the present invention is as follows (LFP):
[0051] Positive electrode preparation:
[0052] Lithium iron phosphate is used as a positive electrode active material, and the positive electrode active material is mixed with polyvinylidene fluoride as a binder and small-particle conductive carbon black (hereinafter referred to as Super P) as a conductive agent in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum stirrer until the system becomes uniform and transparent to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil current collector; the aluminum foil is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0053] Negative electrode preparation:
[0054] Artificial graphite is used as the negative electrode active material, Super P is used as the conductive agent, sodium carboxymethyl cellulose (CMC-Na) is used as the thickener, and styrene-butadiene rubber (SBR) is used as the binder, which are mixed in a mass ratio of 96:1:1:2, and deionized water is added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil is dried at room temperature and then transferred to an oven for drying, and then cold pressed and cut to obtain the negative electrode sheet.
[0055] Electrolyte preparation:
[0056] In an argon atmosphere glove box with a water content of <10ppm, battery-grade (referring to the purity level that meets the battery performance requirements) ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a mass ratio of 1:1:1 to form an organic solvent. The electrolyte is LiPF6, and the total content of LiPF6 is 15% of the total weight of the electrolyte.
[0057] Diaphragm preparation:
[0058] A 12 μm thick polypropylene film (PP) was used as a separator. The positive electrode, separator, and negative electrode prepared above were stacked in sequence, so that the separator was placed between the positive and negative electrodes to play a role of isolation. Then, the aluminum-plastic film was wrapped outside, transferred to a vacuum oven for drying at 120°C, and the electrolyte prepared above was injected at 3.0 g / Ah, then sealed, and the electrolyte was formed, and finally a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1 Ah was prepared.
[0059] A second aspect of the present invention provides an electronic device comprising the secondary battery as described above.
[0060] Exemplarily, the electronic device described in the present invention may be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, a video recorder, a portable printer / copier, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system and a backup power supply, etc.
[0061] In the present application, "%" means weight percentage unless otherwise specified.
[0062] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0063] The lithium ion batteries of Examples 1-6 and Comparative Examples 1-2 are prepared by the following method:
[0064] (1) Preparation of positive electrode sheet
[0065] Lithium iron phosphate is used as a positive electrode active material, and the positive electrode active material is mixed with polyvinylidene fluoride as a binder and small-particle conductive carbon black (hereinafter referred to as Super P) as a conductive agent in a weight ratio of 95:2.5:2.5, and N-methylpyrrolidone (NMP) is added. The mixture is stirred under the action of a vacuum stirrer until the system becomes uniform and transparent to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on a 15μm aluminum foil current collector; the aluminum foil is dried at room temperature and then transferred to a 120°C forced air oven for drying for 1h, and then cold pressed, slit, and finally rolled to obtain a positive electrode sheet.
[0066] (2) Preparation of negative electrode sheet:
[0067] Artificial graphite is used as the negative electrode active material, Super P is used as the conductive agent, sodium carboxymethyl cellulose (CMC-Na) is used as the thickener, and styrene-butadiene rubber (SBR) is used as the binder. They are mixed in a mass ratio of 96:2:1:1 and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on an 8μm negative electrode current collector copper foil; the copper foil is dried at room temperature and then transferred to a 120°C forced air oven for drying for 1h, and then cold pressed and cut to obtain a negative electrode sheet.
[0068] (3) Preparation of electrolyte:
[0069] In an argon atmosphere glove box with a water content of <10ppm, battery-grade (referring to the purity level that meets the battery performance requirements) ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a mass ratio of 1:1:1 to form an organic solvent. The electrolyte is LiPF6, and the total content of LiPF6 is 15% of the total weight of the electrolyte.
[0070] (4) Lithium-ion battery preparation:
[0071] A 12 μm thick polypropylene film (PP) was used as a separator. The positive electrode sheet, separator, and negative electrode sheet prepared above were stacked in sequence, so that the separator was placed between the positive electrode sheet and the negative electrode sheet to play a role of isolation. Then, the aluminum plastic film was wrapped outside, transferred to a vacuum oven at 120°C for drying, and the above-prepared electrolyte 3.0 g / Ah was injected and sealed, and the electrolyte was formed, and finally a soft pack battery (i.e., lithium-ion battery) with a capacity of 1 Ah was prepared.
[0072] In addition to the above-mentioned preparation methods, different parameter conditions involved in the preparation process of the lithium ion batteries of Examples 1-7 and Comparative Examples 1-2 are selected as follows:
[0073] Example 1
[0074] The single-sided coating amount a1 of the positive electrode material layer in this embodiment is 45 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 20 g / m 2 , a1:a2 is 2.25:1, the NP ratio is 1.2:1, the thickness of the positive electrode material layer is 42 μm, and the thickness of the negative electrode material layer is 15 μm.
[0075] Example 2
[0076] The single-sided coating amount a1 of the positive electrode material layer in this embodiment is 45 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 25 g / m 2 , a1:a2 is 1.8:1, the NP ratio is 1.5:1, the thickness of the positive electrode material layer is 42μm, and the thickness of the negative electrode material layer is 17μm.
[0077] Example 3
[0078] The single-sided coating amount a1 of the positive electrode material layer in this embodiment is 45 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 30 g / m 2 , a1:a2 is 1.5:1, the NP ratio is 1.8:1, the thickness of the positive electrode material layer is 42 μm, and the thickness of the negative electrode material layer is 19 μm.
[0079] Example 4
[0080] The single-sided coating amount a1 of the positive electrode material layer in this embodiment is 45 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 18 g / m 2 , a1:a2 is 2.5:1, the NP ratio is 1.08:1, the thickness of the positive electrode material layer is 42 μm, and the thickness of the negative electrode material layer is 14 μm.
[0081] Example 5
[0082] The single-sided coating amount a1 of the positive electrode material layer in this embodiment is 50 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 34 g / m 2 , a1:a2 is 1.47:1, the NP ratio is 1.84:1, the thickness of the positive electrode material layer is 46 μm, and the thickness of the negative electrode material layer is 26 μm.
[0083] Example 6
[0084] The single-sided coating amount a1 of the positive electrode material layer in this embodiment is 70 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 26 g / m2 , a1:a2 is 2.69:1, the NP ratio is 1:1, the thickness of the positive electrode material layer is 61 μm, and the thickness of the negative electrode material layer is 35 μm.
[0085] Example 7
[0086] The single-side coating amount a1 of the positive electrode material layer in this embodiment is 90 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 34 g / m 2 , a1:a2 is 2.65:1, the NP ratio is 1.02:1, the thickness of the positive electrode material layer is 76.5 μm, and the thickness of the negative electrode material layer is 43.5 μm.
[0087] Comparative Example 1
[0088] The single-sided coating amount a1 of the positive electrode material layer in this embodiment is 40 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 30 g / m 2 , a1:a2 is 1.33:1, and the NP ratio is 2.03:1.
[0089] Comparative Example 2
[0090] The single-sided coating amount a1 of the positive electrode material layer in this embodiment is 40 g / m 2 The single-sided coating amount a2 of the negative electrode material layer is 15 g / m 2 , a1:a2 is 2.67:1, and NP ratio is 1.01:1.
[0091] Effect Example 1
[0092] 1. High temperature performance test
[0093] Using the Xinwell CTE-8008-5V200A device and the conventional method in the art, the capacity recovery rates of Examples 1-7 and Comparative Examples 1-2 were tested at 100% SOC and 45°C for 30 days. The capacity recovery rate is the capacity on the 30th day divided by the capacity on the 1st day, and the results are shown in Table 1.
[0094] 2. Low temperature performance test
[0095] Using conventional methods in the art, under the conditions of 5C and discharge for 10s, the DCR at -20°C and 0°C were tested respectively. The results are shown in Table 1.
[0096] Table 1 shows the high temperature performance and low temperature performance of Examples 1-7 and Comparative Examples 1-2.
[0097] Table 1
[0098] Example Capacity recovery rate after 30 days at 45℃ -20℃DCR mΩ 0℃DCR mΩ Example 1 95% 58 15 Example 2 91% 54 12 Example 3 90% 55 14 Example 4 96% 52 14 Example 5 90% 65 18 Example 6 97% 70 22 Example 7 88% 75 26 Comparative Example 1 82% 56 13 Comparative Example 2 83% 53 10
[0099] As can be seen from Table 1, under the condition of 45°C after 30 days, the capacity recovery rate of Examples 1-7 can be maintained at more than 88%, which is better than the capacity recovery rate of Comparative Examples 1 and 2; among them, the capacity recovery rate of Examples 1, 4 and 6 can reach 95% and above. In addition, the low-temperature performance of Examples 1-7 is better, among which the DCR of Example 1-4 at -20°C can be maintained at 58mΩ or less, and the DCR at 0°C can be maintained at 15mΩ or less.
[0100] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A secondary battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector; It is characterized in that The single-sided coating amount a1 of the positive electrode material layer is 45-120 g / m 2 ; The single-sided coating amount a2 of the negative electrode material layer is 15-50 g / m 2 ; The a1:a2 is (1.4-3):
1.
2. The secondary battery according to claim 1, wherein: The single-sided coating amount a1 of the positive electrode material layer is 45-90 g / m 2 .
3. The secondary battery according to claim 1, wherein: The single-sided coating amount a2 of the negative electrode material layer is 15-35 g / m 2 .
4. The secondary battery according to claim 1, wherein: The a1:a2 is (2-3):
1.
5. The secondary battery according to claim 1, wherein: The value range of NP ratio is (1-2):1, The NP ratio is the ratio of the capacity of the negative electrode sheet to the capacity of the positive electrode sheet.
6. The secondary battery according to claim 5, characterized in that: The NP ratio ranges from (1-1.2):
1.
7. The secondary battery according to claim 1, wherein: The thickness of the positive electrode material layer ranges from 42 to 76.5 μm.
8. The secondary battery according to claim 1, wherein: The thickness of the negative electrode material layer ranges from 14 to 43.5 μm.
9. The secondary battery according to claim 1, wherein: In the positive electrode material layer, the positive electrode active material includes one or more of lithium iron phosphate material, lithium iron manganese phosphate material, nickel-cobalt-manganese ternary material and lithium-rich manganese-based material; In the negative electrode material layer, the negative electrode active material includes one or more of crystalline carbon, amorphous carbon, carbon-coated graphite, and resin-coated graphite.
10. An electronic device, characterized in that: It comprises the secondary battery as claimed in any one of claims 1 to 9.
